Unijne uwarunkowania publicznego prawa gospodarczego - Kiczka, Karol (Studia Prawa Publicznego, 2024)
The aim of the study is to present the influence and importance of European Union law on the development of public economic law in Poland. This impact was undoubtedly very significant – it changed in the pre-accession period and after Poland’s accession to the EU and covered many areas. The science of public economic law has long addressed current issues concerning the impact of EU law as well as the acquis communautaire of the European Union on the subject matter of this particular discipline of jurisprudence. The interest in European (EU) topics affected domestic legal studies as a whole and was, for understandable reasons, also applied by other scientific disciplines from their own respective research perspectives. Even in the previous socio-political-economic system, in the period of the Polish People’s Republic, scholars dealing with current public economic law analyzed systemic and specific (detailed) issues of various types, which is confirmed by a review of the literature. Undoubtedly, this influence of legal norms and the EU acquis, both in the pre-accession period and then in the period of EU membership, has increased significantly and has transformed the legal order. These changes concern both the legal situation of entrepreneurs and the position (status) of public authorities, especially economic administration bodies, and the entire mechanism of implementing the multicentric legal system in the social market economy. Substantive, procedural and organizational norms have been transformed, which at the same time sometimes required a revision of previous research attitudes. However, this has definitely opened up new prospects for scientific cognition and teaching in the university world and significantly influenced economic turnover